Genetic of stranded Dugong dugon (Müller 1776) in the Java Sea, Indonesia, through COX1-based DNA barcoding - CITRA SATRYA UTAMA DEWI; SLAMET WAHYUDI; HAGUS TARNO; DEWA GEDE RAKA WIADNYA; FENI IRANAWATI; SUKANDAR SUKANDAR; ANIK MARTINAH; LALU M. IQBAL SANI; BEGINER SUBHAN; SEKAR MIRA HERANDARUDEWI; ELOK FAIQOH; GATOT CIPTADI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Dewi CSU, Wahyudi S, Tarno H, Wiadnya DGR, Iranawati F, Sukandar, Martinah A, Sani LMI, Subhan B, Herandarudewi SM, Faiqoh E, Ciptadi G. 2025. Genetic of stranded Dugong dugon (Müller 1776) in the Java Sea, Indonesia, through COX1-based DNA barcoding. Biodiversitas 26: 951-962. The dugong (Dugong dugon (Müller 1776)), an endangered herbivorous marine mammal, is listed as the Red List of the IUCN and CITES Appendix I. Considering its protected categorizing, its population is persistently decreasing globally, particularly in Indonesia, accordingly requiring significant conservation measures. This study aimed to assess the conservation status of the species, analyze the morphology, morphometry, and genetic profile of stranded dugongs, and evaluate surrounding seagrass meadows. Fieldwork undertaken in February, March, and September 2023 concentrated on stranded dugongs, gathering morphological, morphometric, and genetic data, in addition to surveying seagrass habitats using satellite photography. Morphological observations encompassed 14 criteria, whilst tissue samples from pectoral fins were utilized for genetic profiling by phylogenetic analysis. Geographic coordinates identified stranded dugongs, whereas seagrass regions were assessed with Sentinel-2 data and QGIS. The results indicated that genetic investigation verified the species' strong affinity with populations in the Java Sea and New Zealand, with more divergence from dugongs in Kerala, India. The seagrass beds adjacent to the dugongs' habitat ranged from 0.21 to 16.68 hectares within a larger network of 55.38 to 85.35 hectares, underscoring their potential as a protection zone. These findings underscore the essential link between dugong conservation and seagrass ecosystem conservation, making it clear that both aspects are interconnected and necessitate combined protection methods.